TINJAUAN HUKUM ISLAM TERHADAP PROBLEMATIKA PETANI MUSLIM DALAM PRAKTIK AKAD UTANG PIUTANG USAHA BIBIT BUAH KENTANG DI DESA KALIANYAR KECAMATAN IJEN KABUPATEN BONDOWOSO - Budi Sufyanto (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
In social life, humans cannot be separated from business life, and Islam has transformed into an economic system that has rules as a natural resource with one of the factors that supports the availability of daily necessities. And in that life there are many cases/practices that we can take advantage of, both practices that are prescribed according to Islam or not. Legally, Qardh means giving anything of value to others so that the second party can enjoy the same benefits with the condition that the same or similar amount of the goods must be paid back when requested or at a predetermined time. Likewise with one of the cases that commonly occurs in the community of Sempol Village, Ijen District, Bondowoso Regency, where the majority of the community has practiced debt with potato seeds to the boss and the farmers must pay it with conditional potato harvests (quality) so that the boss will sell the potato harvest and the boss himself directly deducts the amount of money from the potato harvest without telling in detail how much the price per kilo of potatoes is and the total income. As the researcher has explained, the researcher here uses a qualitative research method whose research method is used to research natural objects. This qualitative approach is descriptive in the form of images, not numbers, and the researcher will go directly to the field to directly research how the practices that have occurred in society so that the researcher will get concrete data regarding the case of the debt-credit practice.